(untitled) (Annals of Medical Research, 2024)
Aim: Gastrointestinal stents are predominantly used for palliating malignant dysphagia in patients with esophageal cancer when surgical intervention is deemed inappropriate. This research aims to elucidate the diagnostic and follow-up processes of patients who underwent stent placement for upper gastrointestinal system pathologies at our clinic. Materials and Methods: A retrospective analysis assessed 61 patients who received stents for upper gastrointestinal tract stenosis due to various causes. Patient demographics, including age and gender, underlying pathology, benign-malignant status, location of the pathology, prior surgical or bougie dilation interventions, post-stent survival status, and, if applicable, the duration between the procedure and decease, were evaluated. Patient health records were accessed from the hospital’s electronic medical database. Results: Pre-stent bougie dilation was performed in 26.2% (n=16) of patients, while pre-stent surgery was undertaken in 41% (n=25). Repeat stenting was necessitated in 6.6% (n=4) of cases. Of the patients, 86.9% (n=53) succumbed to their condition, while 13.1% (n=8) survived. Post-stent survival times for deceased patients after stent surgery ranged from 0 to 55 months, with a median survival time of two months. Surviving patients exhibited varied post-stent durations between 65 and 122 months, with a mean stent utilization period of 101 months. A statistically significant correlation was observed between pre-stent surgery and survival status, indicating a higher surgery rate in patients who survived than those who did not (p<0.05). Conclusion: Consequently, due to its cost-effectiveness, stents can be a viable alternative to surgery for both benign and malignant gastrointestinal disorders. This is attributed to its notable advantages, including flexibility and high resistance.